Association between health literacy and sugar-sweetened beverages consumption among Filipinos - Aguilar, Michelle Ann D.
Background: Sugar-sweetened beverages (SSBs) are a common part of Filipino meals. Increase SSB consumption is linked to weight gain and increased risk of noncommunicable diseases (NCDs). Previous studies have shown that health literacy (HL) is associated with positive health outcomes. However, there are limited studies examining its relationship with specific dietary behavior, including SSB consumption.